Developing Effective Strategies and Innovations Targeting the Scabies Parasite (Sarcoptes Scabiei) - Nawar Jaber Hussein Al-asadi (Universitas Negeri Malang, 2026)
Scabies, caused by the scabies mite Sarcoptes scabiei, is a major global health challenge due to limited treatment options and increasing parasite resistance. Ag₂O NPs were prepared using an environmentally friendly green manufacturing method that utilized three extracts: lemon peel oil, aloe vera gel, and colocynth seed extract. Their efficacy against scabies in BALB/c mice was investigated. The nanoparticle formulations were used to treat 60 infected mice, divided into groups, and their efficacy was compared to that of the acaricide benzyl benzoate. LO-Ag₂O Nps demonstrated the highest efficacy in eliminating the parasites, and quantitative polymerase chain reaction (qPCR) results showed a significant increase in the cycle threshold (Ct) value ≥ 35 in the treated mouse group. This is consistent with histological examination, which revealed significant skin healing, and microscopic examination of skin scrapings, which showed no parasites. qPCR results for both (CC-Ag2O and AV-Ag2O) NPs samples groups resulting in a (Ct) of less than 35, indicating a lower percentage reduction in parasites compared to LO-Ag₂O and benzyl benzoate. This was further confirmed by microscopic examination and histological examination, which revealed the absence of the parasite in LO-Ag₂O and benzyl benzoate. These results highlight the potential of plant derived Ag2O NPs formulations as safe and effective alternatives to conventional acaricides, and thus their use in initiating scabies control programs in resource limited settings.